Budaya Flexing di Media Sosial dalam Perspektif Teori Behaviour - Esa Tedja Mahananie (Sekolah Tinggi Teologi Bethel Ambon, 2024)
Flexing culture on social media has become a visible phenomenon in contemporary digital society. This behavior refers to the display of wealth, luxury goods, lifestyle, achievements, or symbolic status to gain attention and social recognition. This article analyzes flexing culture through the perspective of behavioral theory, especially operant conditioning, social reinforcement, and reward learning. Using a conceptual literature-based approach, this article argues that flexing can be understood as a learned and repeated behavior because the digital environment provides immediate social feedback. Likes, comments, shares, followers, and visibility may function as social rewards that reinforce repeated self-presentation. Recent studies show that social media engagement follows reward-learning mechanisms, while online social feedback, influencer exposure, fear of missing out, materialism, and social comparison are related to conspicuous consumption. However, behavioral theory also has limitations because it tends to focus on observable behavior and does not fully explain symbolic meaning, class inequality, platform algorithms, and digital consumer culture. Therefore, flexing culture should be understood as both reinforced behavior and a socio-cultural practice shaped by social media logic, status competition, and conspicuous consumption.